COVID-19 and Education : The impacts on higher education from the confrontations, potentialities and future perspectives - Oliveira, Amanda Rosin de; Dreissig, Ana Helena; Wedekin, Gabriela Oliveira (Revista Nacional de Gerenciamento de Cidades, 2021)
The transformations caused by the COVID-19 pandemic affected people’s routines and lifestyles on a global scale, especially regarding the role of technology. This becomes clear when we examine the state of education currently. The sudden suspension of traditional teaching and the critical aspect in the academy may be the perfect opportunity for a new examination of the potentials and challenges higher education currently faces. This article aims to circumscribe the pandemic’s impacts on higher education and its constituents: students, professors, and educational institutions, after this great increase in technology’s role in people’s daily lives. This is materialized from a bibliographic review by the presented studies of Educação Vigiada "education monitored" (2020), GAFAM’s monopoly over digital education platforms, and how data colonialism comes unnoticed as a consequence of the new technology-focused lifestyles. It was sought to draw a panorama from the opinions of students and teachers, through the SEMESP (2020) survey, pointing to the challenges and potentialities that will help in the adaptation of education in the future context.